Adsorptive removal of eriochrome black T (EBT) dye by using surface active low cost zinc oxide nanoparticles: A comparative overview. (September 2021) - Kaur, Yesbinder; Jasrotia, Teenu; Kumar, Rajeev; Chaudhary, Ganga Ram; Chaudhary, Savita
Abstract: The ecological toxicity imparted by non-biodegradable organic dyes has been considered as a major risk to handle in front of mankind. In this view, the low-cost zinc oxide nanoparticles (ZnO-NPs) were facially synthesized by coating the surface with surfactant (CTAB) and ionic liquid (BMTF) molecules for the effective removal of Eriochrome Black T (EBT) from aqueous media. Various advanced characterization techniques have given insight into the morphological features, crystalline structure and physio-chemical properties of as-synthesized ZnO-NPs. The systematic analysis of the adsorption isotherms and kinetics models specifies that the adsorption of EBT follow Freundlich model and pseudo-second-order kinetics. The intraparticle diffusion model displayed a linear relationship (R 2  = 0.98, 0.97 and 0.94 for BMTF@ZnO, CTAB@ZnO and bare ZnO-NPs), which shows that pore diffusion rate is affected by surface modification and effects the overall EBT adsorption process. Furthermore, after the removal of 87% and 84% of EBT dye by BMTF@ZnO-NPs and CTAB@ZnO-NPs, the fabricated nanoadsorbents of ZnO were successfully regenerated and reused after the treatments up to four times. The adsorption aptitude of ZnO-NPs towards EBT dye was systematically explored in real wastewater samples and interference study of inorganic metallic salts was also performed. The toxicity estimations of the treated dye solutions were made using floral and fungal activities, to ascertain their non-toxic nature before releasing into the environment. These outcomes have supported the immense potential of ZnO-NPs towards the removal of EBT in a cost effective manner. Highlights: Fabrication of ZnO Nps by using cost-effective and greener approach. Detailed investigation showed the effect of surface functionalization during EBT dye removal. Suitable nano adsorbents for real sample analysis established by adsorption isotherms and kinetics models. Plausible mechanism involving the participation of electrostatic interactions and functional groups is discussed. Toxicity reduction estimation using seeds of Vigna radiata and Bjerkandera adusta.